Metal contents in Glycine max (L.) merr. from seven provinces of China (Bangladesh Journal of Botany, 2015)
The black soybean (Glycine max (L.) Merr.) native to China contains rich protein, fat and vitamins. A total of 24 trace elements in black bean from Zhejiang, Heilongjiang, Hebei, Inner Mongolia, Henan, Hainan and Fujian provinces of China were determined by ICP-MS and AAS. Black beans were found to contain beneficial trace elements such as K, Mg, Ca, Zn, Fe and Mn for human health,. The heavy metal concentration in black beans are much low, which proves that black bean is a safe food. The qualities of black beans from the north provinces are higher than south provinces. DOI: http://dx.doi.org/10.3329/bjb.v44i1.22740 Bangladesh J. Bot. 44(1): 151-154, 2015 (March)